Термоэлектрическое устройство для терморефлексотерапии - Kushneryk, L. Ya.; Demchuk, B. M.; Seredyuk, A. I. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A design and circuit solution of a multichannel autonomous device for thermoreflexotherapy has been developed. A significant feature of this device is the use of thermoelectric micromodules with a processor-based method of control and programming of operating modes. Clinical trials have demonstrated the effectiveness of the device.